Faktor Pembelajaran Pendidikan Islam dalam Kurikulum Merdeka - Sembiring, Yana Juhri Artika; Dahlan, zaini (Institut Syekh Abdul Halim Hasan Binjai, 2025)
This research aims to explore the factors that influence Islamic Education learning in the Independent Curriculum Context. The research method used is this research approach will use literature analysis as the main methodology. The initial step involves identifying related literature through academic databases such as Google Scholar, JSTOR, and ProQuest using keywords such as